2007
DOI: 10.1562/0031-8655(2002)0760657dbntal2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary, but not Topical, Alpha-linolenic Acid Suppresses UVB-induced Skin Injury in Hairless Mice when Compared with Linoleic Acid¶

Abstract: Peroxidizability of fatty acids in the air is roughly proportional to the number of double bonds, but in vivo peroxidation proceeds in a more complex manner. Here, we compared the effects of dietary and topically applied oils enriched with linoleic acid (LA, 18:2n‐6) or alpha‐linolenic acid (ALA, 18:3n‐3) on UV‐induced skin injury in a strain of hairless mice. The UVB‐induced erythema score was significantly lower in mice with topically applied creams containing LA and ALA than in mice with the basal cream; no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…Another study showed that EPA and DHA supplements lowered the risk of SCCs (and BCCs) in lung transplant recipients through higher intakes of long-chain omega-3 PUFA were involved than seen in the present study participants [17], or than seen in other studies that showed null results for BCC [41]. The protective effect of α-linolenic acid intake on BCC is unlikely to be due to conversion to EPA or DHA which occurs only to a very limited extent [42][43][44], but rather may result from independent actions such as lowering inflammation markers [45,46] and protecting against photodamage [47]. However, the evidence is sparse and inconclusive, and previous studies have shown little to no effect of dietary intake on BCC [41].…”
Section: Discussioncontrasting
confidence: 51%
“…Another study showed that EPA and DHA supplements lowered the risk of SCCs (and BCCs) in lung transplant recipients through higher intakes of long-chain omega-3 PUFA were involved than seen in the present study participants [17], or than seen in other studies that showed null results for BCC [41]. The protective effect of α-linolenic acid intake on BCC is unlikely to be due to conversion to EPA or DHA which occurs only to a very limited extent [42][43][44], but rather may result from independent actions such as lowering inflammation markers [45,46] and protecting against photodamage [47]. However, the evidence is sparse and inconclusive, and previous studies have shown little to no effect of dietary intake on BCC [41].…”
Section: Discussioncontrasting
confidence: 51%
“…The TBARS assay was carried out according to previously reported methods 73,74 with minor modifications. TBARS assays measure the total level of oxidized lipids based on the reaction of malondialdehyde (MDA), one of the end products of lipid peroxidation, with thiobarbituric acid (TBA).…”
Section: Tbars Assaymentioning
confidence: 99%